Genetic variability of the fatty acid synthase pathway is not associated with prostate cancer risk in the European Prospective Investigation on Cancer (EPIC) - Campa, D; Hüsing, A; Chang-Claude, J; Dostal, L; Boeing, H; Kröger, J; Tjønneland, A; Roswall, N; Overvad, K; Dahm, C; Rodríguez, L; Sala, N; et al. (2011)
A western lifestyle, characterised by low rates of energy expenditure and a high-energy diet rich in animal protein, saturated fats and refined carbohydrates, is associated with high incidence of prostate cancer in men. A high-energy nutritional status results in insulin/IGF signalling in cells, which in turn stimulates synthesis of fatty acids. We investigated whether the genetic variability of the genes belonging to the fatty acid synthesis pathway is related to prostate cancer risk in 815 prostate cancer cases and 1266 controls from the European Prospective Investigation on Cancer (EPIC). Using a tagging approach and selecting 252 SNPs in 22 genes, we covered all the common genetic variation of this pathway. None of the SNPs reached statistical significance after adjusting for multiple comparisons. Common SNPs in the fatty acid synthase pathway are not major contributors to prostate cancer risk. © 2010 Elsevier Ltd. All rights reserved.